Risk Stratification and Prognostication in Delayed PCI: Insights from Grace, TIMI Scores, and Biomarkers - Patel, Jignesh; Natarajan, Karthik; Raval, Pratik (Journal of Neonatal Surgery, 2025)
Background: Risk stratification is crucial in the management of non–ST-segment elevation myocardial infarction (NSTEMI), informing decisions on whether to pursue early or delayed percutaneous coronary intervention (PCI). The Global Registry of Acute Coronary Events (GRACE) and Thrombolysis in Myocardial Infarction (TIMI) scores are frequently used to predict outcomes. Additionally, biomarkers such as serum lactate may offer further prognostic insights in patients undergoing delayed PCI. Methods: This prospective observational study included 120 NSTEMI patients who underwent PCI at least 24 hours after the index event. GRACE and TIMI scores were calculated upon admission, and serum lactate levels were measured pre- and post-procedure. Echocardiographic parameters including ejection fraction (EF) and global longitudinal strain (GLS) were used to assess functional recovery. Results: High GRACE scores (≥141) were observed in 63.33% of patients, and high TIMI scores (≥5) in 67.5%. Despite this elevated risk profile, 80.0% had normal lactate levels (≤2 mmol/L) pre-procedure and 84.17% post-procedure (p<0.05). EF improved from 39.0±9.8% at baseline to 41.7±8.96% post-PCI, while GLS also showed significant gains in most categories. Mortality was 4.17%, predominantly in patients with both high GRACE/TIMI scores and elevated lactate levels. Conclusion: In delayed PCI for NSTEMI, elevated GRACE and TIMI scores identify patients at higher risk, yet significant improvements in EF, GLS, and lactate clearance are achievable in many cases. Combining conventional risk scores with biomarkers such as lactate may enhance prognostication and guide the timing of intervention. Further research is warranted to refine risk models and optimize outcomes in this late-presenting population.